2009
DOI: 10.1542/peds.2008-3150
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Young Children in the Emergency Department: Use of Computed Tomography

Abstract: For young children presenting to the ED with headache but normal neurologic examination findings and nonworrying history, CT scans seldom lead to diagnosis or contribute to immediate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 25 publications
2
40
3
1
Order By: Relevance
“…Most of the time, one can ferret out who has tumor, bleed, or other serious secondary headache disorder from those with exacerbation of migraine or chronic daily headache. We therefore do not advocate routine ER imaging for those patients at low risk for secondary headache when they present …”
Section: Er and Inpatient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time, one can ferret out who has tumor, bleed, or other serious secondary headache disorder from those with exacerbation of migraine or chronic daily headache. We therefore do not advocate routine ER imaging for those patients at low risk for secondary headache when they present …”
Section: Er and Inpatient Managementmentioning
confidence: 99%
“…We therefore do not advocate routine ER imaging for those patients at low risk for secondary headache when they present. 72 There have been multiple papers describing successful approaches to treatment of status migraine in both the emergency setting, as well as the inpatient setting. 73,74 Careful sequential use of medications used in the adult setting has been tried in children without a systemic prospective study.…”
Section: Er and Inpatient Managementmentioning
confidence: 99%
“…1,4 Thus, neuroimaging is considered unnecessary in the diagnosis of headache when no other neurologic symptoms are present to suggest serious intracranial pathology. 1,[5][6][7][8][9][10][11][12][13] Not only is neuroimaging clinically unnecessary for children with isolated headache, it is also associated with potential long-term health risks. CT scans involve larger doses of radiation than conventional radiographs 14 and have been proposed to increase a child' s lifetime risk of cancer.…”
mentioning
confidence: 99%
“…This study resulted from this advisory group' s initial questions. Previous analyses examined neuroimaging as a diagnostic tool for children with headache, but those studies were performed in pediatric neurology clinics, 7,8,11,13,21 EDs, 3,5,22,23 or an ambulatory care setting. 10 This large-scale retrospective claims analysis sought to determine current, real-world practice patterns in the use of neuroimaging to diagnose pediatric headache.…”
mentioning
confidence: 99%
“…It was found that for young children presenting with headache but normal neurological examination and non-worrying history, CT scans seldom lead to diagnosis or contribute to immediate management. 9 The use of CT scanning in young children should be done very carefully to avoid the hazardous exposure to radiation at a young age.…”
Section: Discussionmentioning
confidence: 99%